Vaccine Vectors Harnessing the Power of Cytomegaloviruses - Ynga-Durand, Mario Alberto (Vaccines (Basel), 2019)
Cytomegalovirus (CMV) species have been gaining attention as experimental vaccine vectors inducing cellular immune responses of unparalleled strength and protection. This review outline the strengths and the restrictions of CMV-based vectors, in light of the known aspects of CMV infection, pathogenicity and immunity. We discuss aspects to be considered when optimizing CMV based vaccines, including the innate immune response, the adaptive humoral immunity and the T-cell responses. We also discuss the antigenic epitopes presented by unconventional major histocompatibility complex (MHC) molecules in some CMV delivery systems and considerations about routes for delivery for the induction of systemic or mucosal immune responses. With the first clinical trials initiating, CMV-based vaccine vectors are entering a mature phase of development. This impetus needs to be maintained by scientific advances that feed the progress of this technological platform.